ANALISA TEGANGAN INSITU PADA BATUAN DENGAN METODE EMISI AKUSTIK DI LABORATORIUM - Abdullah (NIM : 22199029), Faisal
Abstract : The activity of the rock excavations changes insitu stress condition. The Acoustic Emission (AE) method is one of the insitu stress determination by using the Kaiser effect of uniaxial test. The initial stress set up on a rock sample, could be detected by using AE test. The success of Kaiser effect acquisition is dependent on the time interval of the initial stress and the AE test. The stress of Kaiser effect is the peak of the initial stress. From this research, apparently all of the lagging applied times (3, 6 & 24 hours) AE show the stress memory, but unobtainable for the initial stress. The stress memory can be also obtained by the Deformation Rate Analysis (DRA) method, it is based on the bending point of stress-strain curve. Stress-strain curve of the initial stress and the AE test is consistent except for the 1g cyclic for the initial load. In this research, the stress memory detected from the both method (AE and DRA), difference less then 20% toward AE. Therefore, the stress memory has retained in rock samples detected.